Nanocellulose based carbon ink and its application in electrochromic displays and supercapacitors. (9th December 2021) - Brooke, Robert; Fall, Andreas; Borràs, Mateu; Yilma, Dagmawi Belaineh; Edberg, Jesper; Martinez-Crespiera, Sandra; Aulin, Christian; Beni, Valerio
Abstract: Conventional electronics have been highlighted as a very unsustainable technology; hazardous wastes are produced both during their manufacturing but also, due to their limited recyclability, during their end of life cycle (e.g. disposal in landfill). In recent years additive manufacturing processes (i.e. screen printing) have attracted significant interest as a more sustainable approach to electronic manufacturing (printed electronics). Despite the field of printed electronics addressing some of the issues related to the manufacturing of electronics, many components and inks are still considered hazardous to the environment and are difficult to recycle. Here we present the development of a low environmental impact carbon ink based on a non-hazardous solvent and a cellulosic matrix (nanocellulose) and its implementation in electrochromic displays (ECDs) and supercapacitors. As part of the reported work, a different protocol for mixing carbon and cellulose nanofibrils (rotation mixing and high shear force mixing), nanocellulose of different grades and different carbon: nanocellulose ratios were investigated and optimized. The rheology profiles of the different inks showed good shear thinning properties, demonstrating their suitability for screen-printing technology. The printability of the developed inks was excellent and in line with those of reference commercial carbon inks. Despite the lower electrical conductivity (400 S m −1 for the developed carbon ink compared to 1000 S m −1 for the commercial inks), which may be explained by their difference in composition (carbon content, density and carbon derived nature) compared to the commercial carbon, the developed ink functioned adequately as the counter electrode in all screen-printed ECDs and even allowed for improved supercapacitors compared to those utilizing commercial carbon inks. In this sense, the supercapacitors incorporating the developed carbon ink in the current collector layer had an average capacitance = 97.4 mF cm −2 compared to the commercial carbon ink average capacitance = 61.6 mF cm −2 . The ink development reported herein provides a step towards more sustainable printed green electronics.